2011
DOI: 10.1021/jf201913x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat-Inactivated Kefir-Isolated Lactobacillus kefiranofaciens M1 on Preventing an Allergic Airway Response in Mice

Abstract: In this study, we assessed the anti-asthmatic effects of heat-inactivated Lactobacillus kefiranofaciens M1 (HI-M1) and its fermented milk using different feeding procedures and at various dosage levels. The possible mechanisms whereby HI-M1 has anti-allergic asthmatic effects were also evaluated. Ovalbumin (OVA)-allergic asthma mice that have been orally administrated the HI-M1 samples showed strong inhibition of production of T helper cell (Th) 2 cytokines, pro-inflammatory cytokines, and Th17 cytokines in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
2
22
0
2
Order By: Relevance
“…However, features regarding the effects of bacteria remain very important. It has been recently described that one strain of L. kefiranofaciens protects mice in a model of allergy [20] and also in an experimental model of colitis [19], but to our knowledge, our work constitutes the first report of the in vivo immunomodulatory activity of L. kefiri .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, features regarding the effects of bacteria remain very important. It has been recently described that one strain of L. kefiranofaciens protects mice in a model of allergy [20] and also in an experimental model of colitis [19], but to our knowledge, our work constitutes the first report of the in vivo immunomodulatory activity of L. kefiri .…”
Section: Discussionmentioning
confidence: 95%
“…Among kefir yeasts, Kluyveromyces marxianus CIDCA 8154 and Saccharomyces cerevisiae CIDCA 8112 downregulate intestinal epithelial innate response through a mechanism dependent on NF-kB modulation [18]. In the case of lactic acid bacteria retrieved from kefir, L. kefiranofaciens has been proven to ameliorate colitis in a DSS-induced murine model [19] and to produce antiasthmatic effects on ovalbumin-allergic asthma mice [20]. On the other hand, Carey and Kostrzynska [21] showed that L. kefiri attenuates the proinflammatory response in intestinal epithelial cells induced by Salmonella Typhimurium and Hong et al [22] showed its influence on Th1 and proinflammatory cytokines production on macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the anti-allergy effect of K37, the 6-week-old mice were sensitized and challenged with OVA to establish an OVA-induced airway allergy BALB/c mice model according to a published report [16] with slight modifications. The experimental procedure for administration of K37, OVA immunization, and sample collection is summarized in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The ovalbumin- (OVA-) sensitized mouse model of allergic airway inflammation was used in this study and has been described in detail by Lee et al [23] and Hong et al [24]. The mice were fed with 10 mg of VA powder/mouse/day throughout the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the splenocyte cultures followed the procedure described by Hong et al [24]. Briefly, The spleens were removed and placed in 10 mL of RPMI-1640 medium (HyClone, Logan, UT, USA) supplemented with 1% antibiotics (50  μ g/mL penicillin, 50  μ g/mL streptomycin sulfate, and 100  μ g/mL neomycin sulfate; Invitrogen, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%